Advances in Multimodality Cardiovascular Imaging in the Diagnosis of Heart Failure With Preserved Ejection Fraction - Del Torto, Alberico; Guaricci, Andrea Igoren; Pomarico, Francesca; Guglielmo, Marco; Fusini, Laura; Monitillo, Francesco; Santoro, Daniela; Vannini, Monica; Rossi, Alexia; Muscogiuri, Giuseppe; Baggiano, Andrea; Pontone, Gianluca (Frontiers in Cardiovascular Medicine, 2022)
Heart failure with preserved ejection fraction (HFpEF) is a syndrome defined by the presence of heart failure symptoms and increased levels of circulating natriuretic peptides in patients with preserved left ventricular ejection fraction and various degrees of diastolic dysfunction. HFpEF is a complex condition that encompasses a wide range of different etiologies. Cardiovascular imaging plays a pivotal role in diagnosing HFpEF, in identifying specific underlying etiologies, in prognostic stratification and in therapeutic individualization. Echocardiography is the first line imaging modality with its wide availability; it has high spatial and temporal resolution and can reliably assess systolic and diastolic function. Cardiovascular Magnetic Resonance (CMR) is the gold standard for cardiac morphology and function assessment, has superior contrast resolution to look in depth into tissue changes and help identify specific HFpEF etiologies. Nuclear imaging can reliably assess myocardial viability and ischemia; new tracings can also assess the myocardial metabolic profile. Cardiovascular Computed Tomography (CCT) can accurately evaluate coronary artery disease both from an anatomical and functional point of view, but tissue characterization methods have also been developed. The aim of this review is to critically summarize the current uses and future perspectives of echocardiography, nuclear imaging, CT and CMR in patients with HFpEF.